2019
DOI: 10.5812/erms.90960
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Teaching Methods on the Quality of Tooth Preparation by Preclinical Students

Abstract: Background:The success of a restoration in fixed prosthodontics is affected by factors related to the dentist's skills. Objectives: Given the significance of these factors, this study was conducted to explore the effect of traditional and new teaching methods on the quality of tooth preparation by preclinical students. Methods: This study was conducted on 58 preclinical students in year three of their program who were divided into two equal groups and were trained on fixed prosthesis preparation. The first gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The educational live video instruction was created to help students in the course who have trouble with visualization. The results of this study revealed significant differences before and after exposure to the instructional video in terms of (inter‐occlusal distance, rough surface, type of finish line, convergence angle, and height of tooth preparation) and this agrees with other studies which have found that instructional multimedia have the potential to improve dental students’ performance 3,14,15,26 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The educational live video instruction was created to help students in the course who have trouble with visualization. The results of this study revealed significant differences before and after exposure to the instructional video in terms of (inter‐occlusal distance, rough surface, type of finish line, convergence angle, and height of tooth preparation) and this agrees with other studies which have found that instructional multimedia have the potential to improve dental students’ performance 3,14,15,26 …”
Section: Discussionsupporting
confidence: 90%
“…The results of this study revealed significant differences before and after exposure to the instructional video in terms of (inter-occlusal distance, rough surface, type of finish line, convergence angle, and height of tooth preparation) and this agrees with other studies which have found that instructional multimedia have the potential to improve dental students' performance. 3,14,15,26 The inter-occlusal distance, surface and margin roughness, type and depth of finish line, and occlusal convergence may all be measured with more accuracy using the CAD/CAM system. We advise that faculty members' grading practices use knowledge of the requirements for an all-ceramic crown.…”
Section: Discussionmentioning
confidence: 99%
“…Dentistry involves many clinical skills that are acquired primarily in a preclinical environment, by combining various forms of learning, such as artificial models of patients and demonstrations by trainers [17].…”
Section: Introductionmentioning
confidence: 99%